2020
DOI: 10.1109/access.2020.3022845
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Dual Circularly Polarized Antenna With Wideband Operation and High Isolation

Abstract: This paper presents a dual-sense circularly polarized (CP) antenna with compact size, high isolation, and wideband characteristics. The antenna consists of a microstrip patch, an array of parasitic metal plates positioned around the patch, and a 90° branch line coupler as feeding structure. Unlike the conventional design method, we demonstrate that the wide isolation bandwidth can be achieved with an imperfect coupler and imperfect matching at the radiating element. The final design with overall dimensions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Our proposed DCP antenna offers more impedance bandwidth and peak isolation compared to those achieved by antenna in [13]. Similarly, the peak interport isolation performance of our antenna is much better than designs reported in [14][15][16][17][18][19][20][21]. e proposed dual CP antenna with high interport isolation can be used in single (monostatic) antenna-based transceiver architecture to realize single-channel full-duplex or in-band full-duplex (IBFD) communication.…”
Section: Prototype Of Antenna With Integrated Single-mentioning
confidence: 70%
See 1 more Smart Citation
“…Our proposed DCP antenna offers more impedance bandwidth and peak isolation compared to those achieved by antenna in [13]. Similarly, the peak interport isolation performance of our antenna is much better than designs reported in [14][15][16][17][18][19][20][21]. e proposed dual CP antenna with high interport isolation can be used in single (monostatic) antenna-based transceiver architecture to realize single-channel full-duplex or in-band full-duplex (IBFD) communication.…”
Section: Prototype Of Antenna With Integrated Single-mentioning
confidence: 70%
“…e employed isolation technique is based on signal inversion mechanism to suppress the leakage from T x port to R x port. e presented dual CP antenna with high interport isolation Average isolation � 5.0 dB 770 MHz [12] ∼60 dB 399 MHz [13] ≥15.2 dB 50 MHz [14] 35 dB 200 MHz [15] 45 dB 1500 MHz [16] 50 dB 85 MHz [17] 36 dB 1340 MHz [18] 20 dB 300 MHz [19] 20 dB 150 MHz [20] 45 dB 80 MHz [21] 25 dB 900 MHz is work 72 dB 90 MHz…”
Section: Discussionmentioning
confidence: 99%
“…Isolation Gain (dBic) [17] 0.81×0.81 ×0.17 Table 2 shows a comparison between the performance of the proposed antenna and those of the existing wideband dual-CP designs. It is observed that the proposed antenna has a simpler configuration and a considerably wider operational bandwidth as compared to most of the dual-CP antennas with low-profile, e.g., [17], [18], [24], [25]. Differing from the prior designs [26]- [28] that require both a wideband radiator and a wideband feeding structure, the proposed antenna has achieved a wideband dual-CP radiation by a simple combination of a wideband radiator and a conventional hybrid coupler.…”
Section: Fabrication and Measurementmentioning
confidence: 99%
“…An air-substrate patch antenna [17] is fed by a four cross slots via a microstrip-line with multiple matching segments to achieve a dual-CP bandwidth of 16%. In [18], a square patch antenna is surrounded by 12 parasitic metal plates to obtain an operational bandwidth of 16.5%. Another way to improve the operational bandwidth of a dual-CP patch antenna is to combine a broadband radiator and a broadband feeding network to generate orthogonal fields.…”
Section: Introductionmentioning
confidence: 99%
“…But the structure of multilayer substrate is not only unfavorable to fabricate, but also increasing the volume and cost of antenna. In [26], [27], isolation is improved by adding parasitic patches around the same plane as the antenna, but the added parasitic patches in addition to the cost increase, the specific antenna shape needs a specific parasitic patch shape, which is not conducive to the design of the array antenna. A vertical metal wall is used to converge the surface current in the position of the vertical metal wall to achieve high isolation, but the addition of the metal wall makes the profile increase and is not conducive to the fabrication [28].…”
Section: Introductionmentioning
confidence: 99%